The Effect of Compensation, Work Motivation and Work Environment on Job Satisfaction of Hospital Nurses - Agusta Dian Ellina; Sultan; Made Mahaguna Putra (Universitas STRADA Indonesia, 2023)
Background: Nursing as part of hospital services has an integral role that contributes to determining the overall quality of services. In order to improve the quality of hospital services, efforts are needed to improve the quality of nursing services. Purpose: This study aims to determine the influence of compensation, work motivation and work environment on job satisfaction of Jayapura Hospital Inpatient Room Nurses. Methods: This study uses primary data which uses questionnaires and interviews with 186 nurses as a sample from the total number of 350 nurses at Jayapura Hospital. In this study, the researcher used quantitative analysis, multiple linear regression analysis and determination coefficient analysis with the help of SPSS version 23 Results: The results of the study obtained using the T-test and F-test partially showed that the variables of compensation, work motivation and work environment had a significant effect on the job satisfaction of nurses in the inpatient room of Jayapura Hospital. Meanwhile, simultaneously, the three variables, namely compensation, work motivation, and work environment, have a significant effect on the job satisfaction of nurses in the inpatient room of Jayapura Hospital. Conclusion: Simultaneously, compensation, work motivation, and work environment have a positive and significant effect on the job satisfaction of inpatient nurses at Jayapura Hospital.